PENDEKATAN METAKOGNITIF DALAM PEMBELAJARAN MATEMATIKA UNTUK PENCAPAIAN KEMAMPUAN KONEKSI DAN PEMECAHAN MASALAH MATEMATIK SISWA SMA - Desy Ayu Nurasyiyah (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2014)
Background of the investigation is the process involves the full awareness of the learning process is still lacking. As a result, the level of attainment of students' mathematical ability is still not meet the minimum level of mastery learning expected. Among the abilities are still lacking is the ability to connect and solving mathematical problems. This study implements mathematical learning with metacognitive approach and want to see its effect on the attainment of connection capability and mathematical problem solving. The purpose of this study was to see impact of learning mathematics with metacognitive approach to the attainments of students in connection and mathematical problem solving ability. as well as how the students' response to this study. The method used is the method Quasi-experimental when the design is the only post respons control group. Participants of this study were students of class X in High School, is located in Bandung district. Instruments used in the research is a matter of post test connection and problem solving ability, then used also student attitude scale, students daily journal, observation and interview guides. Based on the results we concluded that there was no significant difference to the attainment of the connection and mathematical problem solving ability. Being from the results of the questionnaire, the students daily journal, observation and interviews showed a positive response to the learning of mathematics with metacognitive approach.